Withdrawal notice to: Adult hippocampal neurogenesis and antidepressants effects [COPHAR, 50 2020, 17–24]. (February 2020) - Planchez, Barbara; Surget, Alexandre; Belzung, Catherine
Abstract : This article has been withdrawn: please see Elsevier Policy on Article Withdrawal (http://www.elsevier.com/locate/withdrawalpolicy ). This article has been withdrawn at the request of the editor and publisher. The publisher regrets that an error occurred which led to the premature publication of this paper. This error bears no reflection on the article or its authors. The publisher apologizes to the authors and the readers for this unfortunate error.